Tathawwur al-Tiknūlūjiyā fī Ta‘līm al-Lughah al-‘Arabiyyah: al-Ibtikārāt wa al-Taḥaddiyāt wa al-Furaṣ fī al-‘Aṣr al-Raqamī: The Development of Technology in Arabic Language Learning: Innovations, Challenges, and Opportunities in the Digital Era - Rika Hernawati; Dendy Hermawan (Critical Review of English-Arabic World Journal is an open-access journal published by the Language Development Unit, State Islamic University of Kiai Haji Achmad Siddiq, Jember, 2026)
يشهد تعليم اللغة العربية في العصر الرقمي تحولا ملحوظا نتيجة التطور السريع في تكنولوجيا التعليم. فقد أسهمت الوسائط الرقمية، والمنصات التعليمية الإلكترونية، والتطبيقات التفاعلية، والذكاء الاصطناعي في تطوير أساليب تعليم اللغة العربية، وجعلها أكثر جاذبية ومرونة وفاعلية. يهدف هذا المقال إلى مناقشة تطور التكنولوجيا في تعليم اللغة العربية من خلال إبراز أشكال الابتكار، والتحديات التي تواجه المعلمين والمتعلمين، والفرص المتاحة في البيئة الرقمية. ومن أبرز التحديات ضعف البنية التحتية، وتفاوت الكفاءة الرقمية لدى المعلمين، وقلة المحتوى التعليمي العربي التفاعلي المناسب. ومع ذلك، توفر التكنولوجيا فرصا واسعة لتحسين مهارات الاستماع والكلام والقراءة والكتابة، وتعزيز التعلم الذاتي، وتوسيع الوصول إلى مصادر تعلم اللغة العربية. ويؤكد المقال أن التكنولوجيا ليست بديلا عن دور المعلم، بل وسيلة داعمة تسهم في تحسين جودة تعليم اللغة العربية إذا تم توظيفها بصورة تربوية مناسبة. الكلمات المفتاحية: تكنولوجيا التعليم، تعليم اللغة العربية، العصر الرقمي، الابتكار، التعلم الإلكتروني ABSTRACT Arabic language learning in the digital era has experienced significant transformation due to the rapid development of educational technology. Digital media, online learning platforms, interactive applications, and artificial intelligence have contributed to improving Arabic teaching methods, making learning more attractive, flexible, and effective. This article discusses the development of technology in Arabic language education by highlighting innovations, challenges, and opportunities in the digital learning environment. The main challenges include limited infrastructure, uneven digital competence among teachers, and the lack of appropriate interactive Arabic learning content. However, technology offers broad opportunities to improve listening, speaking, reading, and writing skills, support independent learning, and expand access to Arabic learning resources. This article emphasizes that technology should not replace the role of teachers but should function as a supportive tool to enhance the quality of Arabic language learning when applied appropriately and pedagogically.